Climate-Smart Agriculture in Cocoa: A Training Manual for Field Officers - Dohmen, Manon Mireille; Noponen, Martin; Enomoto, Reiko; Mensah, Christian; Muilerman, Sander (2018)
This training manual has been developed to raise awareness among cocoa farmers in Ghana on the effects of climate change on their cocoa production and to give them tools (in the form of recommendations) to mitigate these (negative) effects. The topics can be used by field/extension officers in addition to topics on good agricultural practices.